Synthesis, computational studies, tyrosinase inhibitory kinetics and antimelanogenic activity of hydroxy substituted 2-[(4-acetylphenyl)amino]-2-oxoethyl derivatives. (1st January 2019) - Rafiq, Muhammad; Nazir, Yasir; Ashraf, Zaman; Rafique, Hummera; Afzal, Samina; Mumtaz, Amara; Hassan, Mubashir; Ali, Anser; Afzal, Khurram; Yousuf, Muhammad Rizwan; Saleem, Muhammad; Kotwica-Mojzych, Katarzyna; et al.
Abstract: The over expression of melanogenic enzymes like tyrosinase caused many hyperpigmentaion disorders. The present work describes the synthesis of hydroxy substituted 2-[(4-acetylphenyl)amino]-2-oxoethyl derivatives 3a–e and 5a–e as antimelanogenic agents. The tyrosinase inhibitory activity of synthesized derivatives 3a–e and 5a–e was determined and it was found that derivative 5c possesses excellent activity with IC50 = 0.0089 µM compared to standard kojic acid (IC50 = 16.69 µM). The presence of hydroxyl groups at the ortho and the para position of cinnamic acid phenyl ring in compound 5c plays a vital role in tyrosinase inhibitory activity. The compound 5d also exhibited good activity (IC50 = 8.26 µM) compared to standard kojic acid. The enzyme inhibitory kinetics results showed that compound 5c is a competitive inhibitor while 5d is a mixed-type inhibitor. The mode of binding for compounds 5c and 5d with tyrosinase enzyme was also assessed and it was found that both derivatives irreversibly bind with target enzyme. The molecular docking and molecular dynamic simulation studies were also performed to find the position of attachment of synthesized compounds at tyrosinase enzyme (PDB ID 2Y9X). The results showed that all of the synthesized compounds bind well with the active binding sites and most potent derivative 5c formed stable complex with target protein. The cytotoxicity results showed that compound 5c is safe at a dose of 12 µg/mL against murine melanoma (B16F10) cells. The same dose of 5c was selected to determine antimelanogenic activity; the results showed that it produced antimelenogenic effects in murine melanoma (B16F10) cells. Based on our investigations, it was proposed that compound 5c may serve as a lead structure to design more potent antimelanogenic agents. GRAPHICAL ABSTRACT: